Coexistence of gastrointestinal stromal tumor and inflammatory myofibroblastic tumor of the stomach presenting as a collision tumor: first case report and literature review. Issue 1 (December 2015) - Shin, Hyeong; Gu, Mi; Kim, Se; Kim, Jae; Choi, Joon
Abstract Collision tumors of the stomach are rare. We report on a case of a collision tumor consisting of a gastrointestinal stromal tumor (GIST) and an inflammatory myofibroblastic tumor (IMT) of the stomach in a 16-year-old female. A polypoid mass located in the distal body of the stomach was observed on abdominal computed tomography. Laparoscopic wedge resection of the stomach and 4d lymph node biopsy was performed. On gross examination, a protruding submucosal mass, measuring 4 × 3.5 × 2.5 cm in size, was detected. Histological examination showed two distinct GIST and IMT component presenting a collision tumor. The small nodular area, composed of CD117-positive spindle cells, was typical of GIST, and the adjacent larger area, composed of myofibroblastic spindle cells with prominent chronic inflammatory cells infiltrate, mainly lymphocytes and plasma cells, had a characteristic appearance of IMT. The 4d lymph node showed metastatic inflammatory myofibroblastic tumor. To the best of our knowledge, this is the first case of a collision tumor consisting of a GIST and an IMT arising in the stomach.